2m-3(5-3m)=3m-15

Simple and best practice solution for 2m-3(5-3m)=3m-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m-3(5-3m)=3m-15 equation:


Simplifying
2m + -3(5 + -3m) = 3m + -15
2m + (5 * -3 + -3m * -3) = 3m + -15
2m + (-15 + 9m) = 3m + -15

Reorder the terms:
-15 + 2m + 9m = 3m + -15

Combine like terms: 2m + 9m = 11m
-15 + 11m = 3m + -15

Reorder the terms:
-15 + 11m = -15 + 3m

Add '15' to each side of the equation.
-15 + 15 + 11m = -15 + 15 + 3m

Combine like terms: -15 + 15 = 0
0 + 11m = -15 + 15 + 3m
11m = -15 + 15 + 3m

Combine like terms: -15 + 15 = 0
11m = 0 + 3m
11m = 3m

Solving
11m = 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
11m + -3m = 3m + -3m

Combine like terms: 11m + -3m = 8m
8m = 3m + -3m

Combine like terms: 3m + -3m = 0
8m = 0

Divide each side by '8'.
m = 0

Simplifying
m = 0

See similar equations:

| 4(4x+3)-3(2x+6)=2(3x-9)+2x-4 | | -4s=-48 | | -12t=60 | | X/140=10/y | | X(2x+4)=-12 | | 9-5x-10=15+6x-9 | | 15x-4=8x+15 | | 2-(3x+1)=-2X+5 | | 4x+48=0 | | 7x=8-8x | | -6x-48=0 | | (x-1)(x-2)(x-4)(x-5)-54=0 | | (x-1)(x-2)(x-4)(x-5)-54= | | 3x-9x^2-84x=0 | | x(x+15)=-56 | | 7a+5=3a+33 | | a^2+b^2+c^2=0 | | a^2+b^2+c^2+3abc=4 | | 2-8y=2y-8 | | a^2+b^2+c^2+4abc=4 | | 12=6(4y+1)-2(7y+7) | | 35n/2n | | f(x)=2x+x^2+3(4x)+17*f(7) | | f(x)=2x+x^2+3(4x)+17*7 | | 8(5u-3)-4(7u+4)=32 | | 4.5x+7-9.5x=2 | | 7(7u-8)=5(u-9)+385 | | 6x-2x-1=5+9(-63) | | -5y^2-27+48y=0 | | 0.3x+15.5=x-7.74 | | -6(x+1)-8=-4(x-3) | | 2(2x-2.2)=9x-4.4 |

Equations solver categories